(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The construction of building, roads, bridge and canal, dam is only possible with the construction material. In this experimental work we are working with some sustainable green insulated material (SGIM) to improve its physical property and to reduce its thermal conductivity (TC). In this experimental work we used Rice husk ash (RHA), Sugar cane husk ash (SHA) and Fly ash (FA) in the percentage of 0%, 2.5%, 5%, 7.5% and 10%. With the partial replacement of Ordinary Portland cement (OPC). First, we did tests on material like fineness test, specific gravity test, water absorption test, workability test, compressive strength test, split tensile test and thermal conductivity test. We provided the coding of concrete based on percentage of insulated waste materials (IWM) used in the experiment. NCC is the normal cement concrete and for Modified cement concrete is MCC. After the modification of concrete when we used the insulated waste material, we got the slump value is gradually decreased by 22%-30%. In the case of compressive strength, it is slightly increased by 14.33%. In split tensile test it is increased by 22.2% to by its normal cement concrete. The main test is to be analyzed thermal conductivity test is reduced by 50.04% by to its normal thermal conductivity value. This value is taken from KD2 pro analyzer. For the future aspect we can use some types of insulated waste material for reduction of thermal conductivity and to enhance the physical property of materials.